2012
DOI: 10.2135/cropsci2012.02.0134
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Use Efficiency in a Genetically Diverse Set of Winter Oilseed Rape (Brassica napus L.)

Abstract: Genetic variation in N uptake and utilization was investigated in a set of geneticaliy diverse oilseed rape {Brassica napus L.) genotypes, including hybrid, modern, and old cultivars and resynthesized lines. A total of 36 genotypes were grown at seven locations with two levels of N supply: no fertilization and optinnal fertilization (between 160 and 220 kg ha"^ N, depending on regional recomnnendations). The hybrid cultivars had the highest yields and the old land races and resynthesized lines had the lowest y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 16 publications
5
55
0
Order By: Relevance
“…In addition, the QTL values detected in Miro (2010) and Bouchet et al (2014) varied between the different trials, demonstrating a strong effect of other environmental factors on Nefficiency loci. In fact, direct selection appears to be a convenient strategy for NUE breeding in rapeseed (Kessel et al 2012), an observation that has also been reported for wheat (Brancourt-Hulmel et al 2005).…”
Section: Breeding Strategies Must Be Oriented To Genotype-by-environmmentioning
confidence: 58%
See 3 more Smart Citations
“…In addition, the QTL values detected in Miro (2010) and Bouchet et al (2014) varied between the different trials, demonstrating a strong effect of other environmental factors on Nefficiency loci. In fact, direct selection appears to be a convenient strategy for NUE breeding in rapeseed (Kessel et al 2012), an observation that has also been reported for wheat (Brancourt-Hulmel et al 2005).…”
Section: Breeding Strategies Must Be Oriented To Genotype-by-environmmentioning
confidence: 58%
“…For instance, Kessel et al (2012) compared the seed yield responses of modern cultivars, hybrids, synthetic B. napus accessions, and old cultivars with changes in N conditions. That study found that selection for high yields indirectly enhanced NUE and that hybrids were the most productive genotypes whatever the N nutrition conditions.…”
Section: Nuementioning
confidence: 99%
See 2 more Smart Citations
“…To date much research on developing breeding strategies to improve NUE focuses on main crops including cereals, such as wheat and maize (e.g., Le Gouis et al 2000;Dawson et al 2011;Han et al 2015) and oilseed crops such as canola and oilseed rape (e.g., Balint and Rengel 2008;Berry et al 2010;Kessel et al 2012). NUE of leafy vegetables such as spinach (Chan-Navarrete et al 2014, lettuce (Kerbiriou et al 2014), or cabbage (Schulte auf'm Erley et al 2010) and NUE of non-leafy vegetable crops such as potato (Ospina et al 2014) receive less attention.…”
Section: Objectives Of the Reviewmentioning
confidence: 99%